PROCESS EXECUTION AS A SOURCE OF KNOWLEDGE (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
Knowledge is the most important asset that companies have in the knowledge economy. Intellectual capital is becoming more important than financial capital. The problem that companies face in the modern hypercompetitive environment is not just how to maintain efficiency on an ongoing basis, but also how to adapt to the ever-changing needs of their clients on an ongoing basis. The article demonstrates how expanding traditional business process management (BPM) in accordance with the concept of dynamic BPM empowers companies with the capabilities of creating new knowledge on an ongoing basis, as well as provides the mechanisms of verifying present knowledge. Enabling limited experimentation and the creation of knowledge in the course of performing business processes allows for the constant creation of practical knowledge. Furthermore, such knowledge is immediately verified by the clients in an objective and impartial manner.